2006
DOI: 10.1292/jvms.68.1125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Addition of Sodium Lauryl Sulfate on Frozen-thawed Canine Spermatozoa

Abstract: ABSTRACT. The addition of Orvus ES paste (OEP) to extender may be essential for preparing frozen dog semen. The major ingredient of OEP is sodium lauryl sulfate (SLS). In this study, we compared the effect of SLS on frozen dog semen with that of OEP. There were no significant differences between the 2-mg/ml SLS group and OEP group concerning sperm motility, viability and the percentage of viable sperm with intact acrosomes after freeze-thawing. These results suggest that the effectiveness of frozen dog semen e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…Furthermore, several studies have reported the usefulness of frozen semen extender containing SLS in several animals (the cow [3], mouse [7], and goat [1,2]). We have also reported previously that addition of 2 mg/ml of SLS to dog semen for freezing led to results similar to those obtained by addition of 0.75% OEP [8]. However, no studies have reported addition of SLS to cat semen for freezing.…”
supporting
confidence: 71%
“…Furthermore, several studies have reported the usefulness of frozen semen extender containing SLS in several animals (the cow [3], mouse [7], and goat [1,2]). We have also reported previously that addition of 2 mg/ml of SLS to dog semen for freezing led to results similar to those obtained by addition of 0.75% OEP [8]. However, no studies have reported addition of SLS to cat semen for freezing.…”
supporting
confidence: 71%
“…In 2009, we investigated the effectiveness and optimal concentration of OEP and its main ingredient, SLS, to cryopreserve cat semen, and found that the addition of OEP or SLS for the cryopreservation of cat semen clearly improved the post-thaw semen quality, compared with no addition, and that the optimal concentrations of OEP and SLS were 1.0% and 3 mg/ml, respectively [9]. The effectiveness of OEP and its main ingredient of SLS as a semen cryoprotectant has also been shown in dogs and pigs [7,8].In this study, we performed IUI with semen that had been cryoprotected by the addition of glycerol and 1% OEP or 3 mg/ml of SLS, and compared its fertilizing ability.Animals: Mixed breed cats bred and maintained in our colony were used. Five male cats aged 2-11 years [mean: 5.6 ± 1.6 years (SE)] and weighing 4.3-5.0 kg (mean: 4.6 ± 0.1 kg) with a normal semen quality, copulation capability, and fertility were used.…”
mentioning
confidence: 93%
“…The addition of detergents such as Equex STM paste, Orvus ES paste, and sodium dodecyl sulfate (SDS) to egg yolk-supplemented extenders appears to have beneficial effects on spermatozoa motility after thawing [ 27 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Although SDS is believed to have effects on membrane fluidity upon interaction with the egg yolk [ 54 ], there are relatively few litters following artificial insemination using the same ( Table 1 ).…”
Section: Extender For Canine Spermatozoamentioning
confidence: 99%